2009
DOI: 10.1016/j.vaccine.2009.07.108
|View full text |Cite
|
Sign up to set email alerts
|

Induction of protective immunity by vaccination against Chlamydia trachomatis using the major outer membrane protein adjuvanted with CpG oligodeoxynucleotide coupled to the nontoxic B subunit of cholera toxin

Abstract: The present study was undertaken to test the efficacy of immunization with the native major outer membrane protein (nMOMP) of C. trachomatis mouse pneumonitis (MoPn) serovar in combination with a novel immunostimulatory adjuvant consisting of CpG oligodeoxynucleotide (ODN) linked to the nontoxic B subunit of cholera toxin (CTB-CpG) to elicit a protective immune response to C. trachomatis. High levels of Chlamydia specific IgG antibodies were detected in the sera from BALB/c mice immunized intramuscularly and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 44 publications
(35 reference statements)
0
27
0
Order By: Relevance
“…Successful examples include fusion of subunit B of LT to a viral protein [287], conjugation of toxoids to capsular polysaccharides of many invasive bacteria such as Streptococcus pneumoniae, H. influenzae type b, meningococci, pneumococci [2,288,289], and conjugation of LT subunits with CpG [111,290]. It should be noted that the bacterial toxins can initiate a strong humoral immune response, which may overshadow the response to the conjugate antigen [7].…”
Section: Toxinsmentioning
confidence: 99%
“…Successful examples include fusion of subunit B of LT to a viral protein [287], conjugation of toxoids to capsular polysaccharides of many invasive bacteria such as Streptococcus pneumoniae, H. influenzae type b, meningococci, pneumococci [2,288,289], and conjugation of LT subunits with CpG [111,290]. It should be noted that the bacterial toxins can initiate a strong humoral immune response, which may overshadow the response to the conjugate antigen [7].…”
Section: Toxinsmentioning
confidence: 99%
“…Second-generation vaccines are subunit immunogens, such as proteins, DNA, RNA, or oligonucleotides, and have been shown to be very promising. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, these secondgeneration vaccines need effective delivery systems to protect their respective immunogens from rapid degradation and to potentiate immunological responses. Biodegradable nanoparticles used as immune potentiators and delivery systems are now playing an increasing role in next-generation vaccine development projects.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Nonetheless, vaccine research with MOMP as the prime immunogen has been both encouraging and disappointing. Previous studies using native MOMP in combination with adjuvant revealed some protective efficacy in vivo, [28][29][30] but the drawback with native MOMP is the expense associated with its production if selected as a candidate vaccine. 16 The use of recombinant MOMP (rMOMP) with conventional adjuvants, including cholera toxin, aluminum, and CpG, to name a few, has been widely explored, but the degree of protection achieved with these vaccines is not as robust as that achieved with native MOMP.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the major outer membrane protein (MOMP) as a vaccine candidate has been extensively studied, with varying success. [72][73][74][75][76][77][78][79] The use of this antigen has resulted from the fact that it constitutes approximately 60% of the outer membrane protein mass of the chlamydial EB. 47 However, MOMP contains four variable domains that are surface exposed and are antigenically variable between serovars.…”
Section: Treatment or Prevention?mentioning
confidence: 99%